Arrival directions of vosmic rays above 32 EeV from phase one of the Pierre Auger Observatory - Micheletti, M. I. (2022)
Fil: Fil: Micheletti, M. I. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Física de Rosario (IFIR-CONICET); Argentina.